Reduced Mortality With Ondansetron Use in SARS-CoV-2-Infected Inpatients. (14th July 2021) - Bayat, Vafa; Ryono, Russell; Phelps, Steven; Geis, Eugene; Sedghi, Farshid; Etminani, Payam; Holodniy, Mark
Abstract: Background: The coronavirus disease 2019 (COVID-19) pandemic has led to a surge in clinical trials evaluating investigational and approved drugs. Retrospective analysis of drugs taken by COVID-19 inpatients provides key information on drugs associated with better or worse outcomes. Methods: We conducted a retrospective cohort study of 10 741 patients testing positive for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection within 3 days of admission to compare risk of 30-day all-cause mortality in patients receiving ondansetron using multivariate Cox proportional hazard models. All-cause mortality, length of hospital stay, adverse events such as ischemic cerebral infarction, and subsequent positive COVID-19 tests were measured. Results: Administration of ≥8 mg of ondansetron within 48 hours of admission was correlated with an adjusted hazard ratio for 30-day all-cause mortality of 0.55 (95% CI, 0.42–0.70; P < .001) and 0.52 (95% CI, 0.31–0.87; P = .012) for all and intensive care unit–admitted patients, respectively. Decreased lengths of stay (9.2 vs 11.6; P < .001), frequencies of subsequent positive SARS-CoV-2 tests (53.6% vs 75.0%; P = .01), and long-term risks of ischemic cerebral ischemia (3.2% vs 6.1%; P < .001) were also noted. Conclusions: If confirmed by prospective clinical trials, our results suggest that ondansetron, a safe, widely available drug, could be used to decrease morbidity and mortality in at-risk populations. Abstract : In this retrospective study of 10, 741 hospitalized COVID-19 infected veterans, we found a significant reduction in mortality among those who received ondansetron during the first 2 days of admission, including those requiring ICU care or with increased comorbidities.